Profil Kesalahan Proses Berpikir Matematis Mahasiswa Berdasarkan Tahapan Berpikir Mason - Ketut Sarjana; Gilang Primajati; Ulfa Lu'luilmaknun; Ni Made Intan Kertiyani; Eka Kurniawan; Dea Nadia (FKIP Universitas Mataram, 2026)
Mathematical proof is an essential competency for prospective mathematics teachers because it is closely related to reasoning and mathematical thinking skills. This study aimed to describe the profile of students' mathematical thinking errors based on Mason's thinking stages, namely entry, attack, and review, in proving mathematical principles on geometric vector topics. A quantitative descriptive approach was employed involving 44 sixth-semester Mathematics Education students. Data were collected through an essay-based mathematical proof test and analyzed using an error analysis rubric based on Mason's thinking stages. Descriptive statistics were used to calculate the frequency and percentage of errors at each stage. The results revealed that the percentages of errors at the entry, attack, and review stages were 18%, 70%, and 82%, respectively. Errors at the entry stage were mainly related to incomplete identification of given information and incorrect mathematical notation, whereas attack stage errors involved difficulties in constructing proof strategies and understanding the angle between vectors. At the review stage, students failed to verify the validity of their proofs and formulate appropriate conclusions. In conclusion, students' mathematical thinking errors were predominantly found at the attack and review stages.